Bilateral environmental aid and trade - Yoon, Sang W.; Kim, Younjun; Park, Byoung G.; Yoon, Chang-Ho (Applied Economics, 2024)
The paper estimates the determinants of the growing volume of bilateral environmental aid for the mitigation of climate change using an empirically testable multilateral framework in which both donors and recipient countries compete in world export markets. As the potential donors weigh environmental benefits against the economic costs of providing aid, strategic interactions between the donors and the recipient countries as well as among the donors, influence the evolution of environmental aid. The paper shows that while the volume of bilateral environmental aid increases with the recipient country’s credible environmental commitment and bilateral trade volume, the competitive pressure in the export market reduces bilateral environmental aid. Free-riding incentives prevail among the individual donors, whereas the multilateral environmental aids that aim to restore the loss of global environmental resources without altering individual trade competitiveness can increase bilateral environmental aids.
_eprint: https://doi.org/10.1080/00036846.2023.2289935
Keywords: Environmental ODA; F18; F35; Q54; competitive threats; credible commitment; dept.eco; international trade; multilateral institutions; peer-reviewed